HEartLight guided – PUre Pulmonary Vein Isolation Regardless of Concomitant Atrial Substrate: HEURECA Study. Issue 1 (29th November 2018) - Nagase, Takahiko; Bordignon, Stefano; Perrotta, Laura; Bologna, Fabrizio; Tsianakas, Nikolaos; Chen, Shaojie; Konstantinou, Athanasios; Chun, Julian K.R.; Schmidt, Boris
Abstract: Background: It remains unclear whether left atrial low‐voltage area (LALVA) affects atrial tachyarrhythmia recurrence after laser balloon pulmonary vein isolation (PVI) for atrial fibrillation (AF). We prospectively evaluated the outcome of laser balloon PVI in patients with and without LALVA (≤ 0.5 mV) together with surface/intracardiac electrophysiological criteria. Methods: One hundred consecutive paroxysmal/persistent AF patients underwent laser balloon PVI. The relative extent of LALVA (extent of LALVA/left atrial surface area × 100 [%]: rLALVA), total p‐wave duration in lead II (PWD), and time interval from the beginning of p‐wave to the local activation in left atrial appendage (TTLAA) were assessed. Patients were divided into patients with LALVA (group A: 23 patients) and those without LALVA (group B: 77 patients). The primary endpoint was freedom from atrial tachyarrhythmia after the blanking periods. Results: Complete PVI was achieved in 99/100 (99%) patients. PWD and TTLAA were longer in group A (both, P < 0.001). During 12 months' follow‐up, survival free from atrial tachyarrhythmia recurrence was lower in group A (12/23 [52%] patients vs 67/77 [87%] patients, P < 0.001). Multivariate analysis identified rLALVA as the only independent predictor of atrial tachyarrhythmia recurrence. rLALVA correlated with PWD and TTLAA (r = 0.41, P < 0.001 and r = 0.60, P < 0.001, respectively). Receiver operating characteristic curve for rLALVA revealed PWD of 122 ms and TTLAA of 92 ms as the optimal cut‐off value. Conclusion: LALVA was associated with poorer outcome after laser balloon PVI. Patients may be identified by longer PWD and TTLAA.